Meningkatkan Softskill Siswa Melalui Model Pembelajaran Project Based Learning dalam Pembelajaran Tematik di Madrasah Ibtidaiyah - Supriyanto; Sari, Dian Septiana Purnama (Universitas KH. Abdul Chalim Pacet Mojokerto, 2024)
The students’ low levels of creativity and critical thinking skills are significant issues that need to be addressed in the face of the rapidly developing modern era. Therefore, an appropriate learning model is required to enhance students’ creativity and critical thinking skills over time. This study focuses on the problem related to the Project-Based Learning model and students’ soft skills. The study aims to determine how the Project-Based Learning model is applied in thematic learning and its effect on the soft skills of fifth-grade students at MI Manbaul Huda. This study employs a pre-experimental research design, specifically the pretest-posttest one-group design, with a population of 27 fifth-grade students. The sample used was saturated, and it included all 27 students. To assess the students’ creativity and critical thinking skills, the research involved administering a test in the form of essays consisting of 10 questions that had been tested for validity and reliability. Hypothesis testing in this study was conducted using a t-test. The results of the hypothesis testing indicated a significance value of 0.000. Since the significance value is less than 0.05, it can be concluded that